Effect of planting dates and nitrogen fertilizer rates on growth, yield and its components of yellow maize hybrids (Zea mays L.) - Essa, Ali Skor; H. Bassiouny, Ameen; M. Abdalla, Maha (Journal of Neonatal Surgery, 2025)
A field experiment was carried out at a Private Farm in Shiba-El-Nakaria Village Destrict, Sharkia Governorate, Egypt during the two successive growing summer seasons of 2023 and 2024 to investigate the effect of three planting dates i.e. 1st May, 15th May and 30th May and four nitrogen fertilizer rates, i.e. 0, 70, 100 and 130 KgN/fed. on yield and its attributes for three yellow maize hybrids, i.e. single cross 168 (S.C.168), 176 (S.C.176) and payoneer 444 (S.C.444) under model Delta conditions in Sharkia Governorate. Results indicated that sowing date on 1st May produced a largest ear leaf area (cm2), leaf area index (L.A.I), plant height (cm), ear height (cm), number of ears/plant, number of ears (m2), ear length (m), ear diameter (cm), number of rows/ear, number of grain/rows, ear weight (g), 100-grain weight (g), straw yield (ton/fed), grain yield (ton/fed) and biological yield (ton/fed) followed by sowing date at 15th May, respectively. The sowing date on 30th May gave the lowest values in this concern. The obtained results indicated that the three maize hybrids differed significantly in all studied traits in the two growing seasons, whereas SCP444 hybrid gave the highest values in all studied traits except 100-grain weight, the hybrid S.C.176 gave the heavest value. Results also showed that significantly increased in all studied traits with increasing the application of nitrogen fertilizer rates from 0 up to 130 KgN/fed. Positive and highly significant correlation coefficient between grain yield and all studied characters i.e. No of ear/plant, No of ear (m2), ear length (cm), ear diameter (cm), No of rows/ear, No of grain/rows, ear weight (gm), straw and biological yield (ton/fed) while 100-grain weight (g) was insignificantly correlated. Conclusively: It be concluded that sowing date at 1st May, Bayoneeer (S.C.P. 444) variety and 130 KgN/fed. caused an increased in growth in maize and yield and its components..